2021
DOI: 10.3892/ijmm.2021.4938
|View full text |Cite
|
Sign up to set email alerts
|

DNAJC12 promotes lung cancer growth by regulating the activation of β‑catenin

Abstract: Lung cancer has become the leading cause of cancer-associated mortality worldwide. However, the under- lying mechanisms of lung cancer remain poorly understood. DnaJ heat shock protein family (HSP40) member C12 (DNAJC12) is a type III member belonging to the HSP40/DNAJ family. The role of DNAJC12 in numerous types of cancer has been previously reported; however, the effect of DNAJC12 in lung cancer remains unknown. The results of the present study indicated that DNAJC12 may be involved in lung cancer prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Using bioinformatics technology, we found that DNAJC12 is upregulated in lung adenocarcinoma (LUAD). Consistently, Li et al (19) recently reported that DNAJC12 was overexpressed in lung cancer, and overexpression of DNAJC12 significantly promoted lung cancer cell growth and migration by increasing β-catenin expression. Noticeably, accumulated evidence has verified that the β-catenin signaling is closely implicated in regulating the aerobic glycolysis and drug resistance in lung cancer (20)(21)(22)(23), suggesting that DNAJC12 may participate in regulating the aerobic glycolysis and drug resistance of lung cancer through activating the β-catenin signaling.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Using bioinformatics technology, we found that DNAJC12 is upregulated in lung adenocarcinoma (LUAD). Consistently, Li et al (19) recently reported that DNAJC12 was overexpressed in lung cancer, and overexpression of DNAJC12 significantly promoted lung cancer cell growth and migration by increasing β-catenin expression. Noticeably, accumulated evidence has verified that the β-catenin signaling is closely implicated in regulating the aerobic glycolysis and drug resistance in lung cancer (20)(21)(22)(23), suggesting that DNAJC12 may participate in regulating the aerobic glycolysis and drug resistance of lung cancer through activating the β-catenin signaling.…”
Section: Introductionsupporting
confidence: 63%
“…Although it has been demonstrated that DNAJC12 was overexpressed and served as an oncogene in lung cancer through regulating β-catenin signaling (19), DNAJC12 roles in modulating aerobic glycolysis and DDP resistance in NSCLC still remain unclear, as well as the underlying mechanisms. In this study, we explored the role of DNAJC12 in aerobic glycolysis and DDP resistance of NSCLC, and studied whether DNAJC12 transcription could be modulated by HNF1A for the first time using both in vitro (cell lines) and in vivo assays through construction of the xenotransplantation model in 6-week-old BALB/c nude mice.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study revealed that DNAJC12 was an estrogen target gene, and high levels of DNAJC12 were found in MCF-7 breast cancer cells after 17beta-estradiol treatment [ 14 ]. In lung cancer, DNAJC12 silencing memorably suppressed lung cancer cell growth, as indicted by a significant reduction in proliferation, colony formation, migration, and invasion and increase in cell apoptosis by modulating β -catenin expression and activation [ 15 ]. Besides, HNF1A enhanced the expression of DNAJC12 in nonsmall cell lung cancer by promoting the transcription of DNAJC12, thus promoting aerobic glycolysis and resistance development of DDP through regulating β -catenin expression [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…And, development of dystonia and intellectual disability in humans is strongly associated with biallelic mutations in the DNAJC12 gene [12]. In recent years, many literature studies have reported that the biological role of DNAJC12 has been gradually found in cancer progression, such as gastric cancer, breast cancer, and lung cancer, and DNAJC12 was involved in cancer cell proliferation, migration, invasion, and drug resistance [13][14][15]. Targeting DNAJC12 in the treatment of RC is still on the way, there are many mechanisms and problems that need to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…In gastric cancer, increased mRNA expression of DNAJC12 is correlated with cancer invasion, lymph node metastasis, and disease progression, thus having higher morbidity and mortality rates [193]. Moreover, in lung cancer, DNAJC12 levels are upregulated, while DNAJC12 knockdown reduces the malignant properties and tumor growth of lung cancer cells in vitro and in vivo by inhibiting activation of β-catenin [194]. However, none of these studies address if there is a link with p53.…”
Section: Other Dnajc Members and Cancermentioning
confidence: 99%